Cognition and social functioning in first episode psychosis: A systematic review of longitudinal studies - Montaner-Ferrer, Maria José; Gadea, Marien; Sanjuán, Julio (Frontiers in Psychiatry, 2023)
This systematic review aimed to answer whether we can predict subsequent social functioning in first episode psychosis (FEP) by means of an initial cognitive examination. In order to do this, we gathered longitudinal studies which evaluated neurocognition and/or social cognition regarding their impact on long-term social functioning of FEP patients. The MOOSE method was employed and 28 studies covering data from a total of 2572 patients with longitudinal trajectories from 2 months to 5 years were reviewed. In general, cognitive deficits impacted on the social functioning of the FEP patients across the time. The neurocognitive domains most closely related to social functioning were processing speed, sustained attention and working memory, and an overall cognitive disfunction, low IQ and academic trajectory were also found predictive. Regarding social cognition, the findings were not unanimous. Moreover, several of the articles found a complex relationship between social cognition, neurocognition, social functioning and negative symptoms, pointing social cognition as a modulator of neurocognition but being modulated as well by negative symptoms. The principal clinical implication of this review is that the initial assessment of FEP patients and their rehabilitation must take cognition into account.